The State Obligation for Stateless Citizens: A Study of Sanger Philippines in Indonesia - Kariana, Lusy; Ashri, Muhammad; Riza, Marwati; Sakharina, Iin Karita (International Journal of Psychosocial Rehabilitation, 2020)
Citizenship not only gives a legal identity, but also the right to obtain legal guarantees and protections from the State, their constitutional rights and other rights as stipulated in national legislation or regulated in international law. The issue of citizenship does not only occur in other countries but also in Indonesia. One of them is a stateless person of Filipino descent living in North Sulawesi Province, especially in Bitung City. The results show that the substance of human rights in the field of economic and social for peoples without citizenship gives the obligation for the State to reduce the status of stateless persons. One of them is through arrangements that ease them to obtain citizenship status. Nationally, there is no specific regulation regarding stateless person in Indonesia, but it is only limited to the regulation of the conditions for obtaining citizens in the citizenship law. The state obligation to fulfill the economic, social and cultural rights of Sanger Philippines citizens in North Sulawesi Province has not been fulfilled due to the bureaucratic, budgetary and cultural obstacles.